Investigation of microstructural development of liquid Nb in dependence of cooling rate: Molecular dynamics simulation study - Kazanc, Sefa; Canbay, Canan Aksu (Pergamon-Elsevier Science Ltd, 2023)
In this study, the microstructural developments in the Niobium (Nb) bulk system cooled with different cooling rates from the liquid phase were investigated by the Molecular Dynamics (MD) method. The Embedded Atom Method (EAM), which includes many-body interactions, was used to calculate the interaction forces between atoms. The microstructural changes in the model system were tried to be determined by radial distribution function (RDF), voronoi polyhedra analysis (VP), determination of folded symmetries, spherical periodic order (SPO) and atomic images obtained from common neighbor analysis (CNA). Glassy structure transformations were observed for 1 x 1014 K/s, 5 x 1013 K/s, 1 x 1013 K/s cooling rates applied to the liquid Nb system, and crystal structure transformations were observed under 0 GPa pressure for 5 x 1012 K/s and 2 x 1012 K/s cooling rates. In addition, the glassy and crystalline transition temperatures at which these transformations take place were calculated. While an increase was observed in 5-fold symmetries expressing icosahedral short distance order in glassy structures obtained as a result of cooling processes, a decrease in 5-fold symmetries and an increase in 4 and 6-fold symmetries were determined in crystal structure transformations.
Keywords: Rapid cooling; Voronoi analysis; Molecular dynamics; Glassy formation